«Философская антропология М. Шелера: актуальность в современном мире» - Черкашин, В. А. (ХНУРЕ, 2019)
In this article live lundamental anthropology ideas about human development are described. Philosophical anthropology problems about establishment of language, state, science and culture in connect with structure of social being are determined. The role of transformation of social morals in mankind’s surviving is distinguished.